Implantable cardioverter defibrillator therapy in young patients with cardiomyopathies and channelopathies: a single Italian centre experience. Issue 7 (July 2016) - Migliore, Federico; Silvano, Maria; Zorzi, Alessandro; Bertaglia, Emanuele; Siciliano, Mariachiara; Leoni, Loira; De Franceschi, Pietro; Iliceto, Sabino; Corrado, Domenico
Abstract : Aims: This study was designed to prospectively evaluate the risk–benefit ratio of implantable cardioverter defibrillator (ICD) therapy in young patients with cardiomyopathies and channelopathies. Methods and results: The study population included 96 consecutive patients [68 men, median age 27 (22–32) years] with cardiomyopathies, such as arrhythmogenic right ventricular cardiomyopathy ( n = 35), dilated cardiomyopathy ( n = 17), hypertrophic cardiomyopathy ( n = 15), Brugada syndrome ( n = 14), idiopathic ventricular fibrillation ( n = 5), left ventricular noncompaction ( n = 4), long-QT syndrome ( n = 4) and short-QT syndrome ( n = 2), who were 18–35 years old at the time of ICD implantation. During a mean follow-up of 72.6 ± 53.3 months, one patient with end-stage hypertrophic cardiomyopathy died because of acute heart failure, and 11 patients underwent orthotopic heart transplantation. Twenty patients (20.8%) had a total of 38 appropriate ICD interventions (4%/year), and 26 patients (27.1%) experienced a total of 49 adverse ICD-related events (5.4%/year), including 23 inappropriate ICD interventions occurring in nine patients (9.4%) and 26 device-related complications requiring surgical revision occurring in 20 patients (20.8%). Lead failure/fracture requiring lead extraction was the most common complication ( n = 9). A threshold for ICD therapy less than 300 ms was associated with a borderline significant lower probability of inappropriate ICD interventions (hazard ratio = 0.2; 95% confidence interval 0.02–1.2; P = 0.07), whereas underweight status was an independent predictor of device-related complications (hazard ratio = 5.4; 95% confidence interval 1.5–19.4; P = 0.01). Conclusion: In young patients with cardiomyopathies and channelopathies, ICD therapy provided life-saving protection by effectively terminating life-threatening ventricular arrhythmias. However, because ICD-related adverse events are common, the risk/benefit ratio should be carefully assessed when considering ICD implantation in young people.